FROM VALUES TO PRACTICE: THE ROLE OF RELIGIOUS CULTURE IN SHAPING SPIRITUAL INTELLIGENCE AMONG STUDENTS AT ELEMENTARY SCHOOL JEMBER - Muhammad, Zahrul Adyan; Mas'ud, Mas'ud; Sarwan, Sarwan (ATTA`DIB, 2024)
This study aims to analyze the implementation of religious culture in fostering students' spir-itual intelligence at SD Baitul Amien 1 and SD Baitul Amien 2 Jember. The research focuses on strategies for instilling religious cultural values, the development of religious culture pro-grams, and their implications for students' spiritual intelligence. A qualitative approach was used with a case study and multi-case design. Data were collected through interviews, obser-vations, and document analysis. The research subjects were purposively selected, including the principal, vice principal of curriculum, Islamic education teachers, and students. Data analysis followed the Miles, Huberman, and Saldana model, with data validity tested through technique and source triangulation. The findings reveal that: (1) Strategies for instilling reli-gious cultural values are carried out through the development of an integrated curriculum, the creation of a supportive learning environment, and the involvement of all school compo-nents; (2) Religious culture programs include congregational Duha prayer, Monday-Thursday fasting, congregational prayer, prayer habituation, honesty canteens, and the 3S culture (Smile, Greet, Salute); (3) The implementation of religious culture has multidimen-sional implications, encompassing spiritual-personal, social-interpersonal, and academic-intellectual dimensions. This study concludes that a structured and integrated religious cul-ture can be an effective strategy for fostering students' spiritual intelligence in public schools.